(untitled) (Nigerian Journal of Technology, 2018)
Lightning phenomenon has resulted into several losses to both supply-side and load-side of the electricity infrastructure. Quite a handful of research has investigated strategies for its mitigation. This work is an application of the Fernandez-Diaz arrester model to the section of Eko Distribution network. The procedure involves simulation of the network in respect of the influence of the surges and surge arresters using MATLAB/SIMULINK. The study reveals that whenever lightning strikes, the resulting overvoltage causes distortion to the voltage waveform, as well as the current waveform. This indicates the presence of harmonics. Meanwhile, with the installation of the arresters, the overvoltage reduces by 86% at the nearest node of installation. However, at the other nodes within the same branch, the installed arrester attenuated the surge overvoltage by approximately 60%. This suggests that more arresters need to be installed at other nodes along the branch in order to eliminate the occurrence of overvoltage. Moreover, the study reveals that a surge arrester installed at one of the two branches of the network has negligible effect in attenuating voltage surge at the other branch of the same network. http://dx.doi.org/10.4314/njt.v37i2.27